PREVALENSI MIOMA UTERI BERDASARKAN UMUR DI RSUP PROF. DR. R. D. KANDOU MANADO - Pasinggi, Sabrianti; Wagey, Freddy; Rarung, Max (e-CliniC, 2015)
Abstract:Myoma uteriis a benign tumor of the uterine. Insidence of myoma uteri at 20% -30% of all women and continues to increase. The second most common gynecological tumors in Indonesia. Commonly found in women of reproductive age and only 10% of myoma uteri is still growing after menopause. Approximately 60% asymptomatic and almost 50% are found incidentally on gynecologic examination. Objective: to determine the age prevalence of uterine myomas compared with other gynecological tumors in the Prof. Dr R. D. KandouHospital Manado.Methods:Retrospective descriptive study using medical records. Sample of this study is 401 cases of gynecological tumors, 127 of them is cases of myoma uteri in period of July1st2013-July 1st 2014. The data analysis is univariateanalysis.Results and Conclusion: The results of medical recordsin periodJuly 1st 2013-July 1st2014, myoma uteri is the second largest gynecological tumors (31.7%). Based on 127 cases,the suffered most from of myoma uteri is the age between 41-50 years (56.7%). The highest prevalence of uterine myoma in the age between 41-50 years (48.9%).Keywords: gynecological tumors, myoma uteri, prevalence, ageAbstrak: Mioma uteri adalah tumor jinak pada uterus. Insidensinya sekitar 20%-30% dari seluruh wanita dan terus mengalami peningkatan. Tumor ginekologi kedua terbanyak di Indonesia. Umumnya ditemukan pada wanita usia reproduksi dan hanya 10% miomauteriyang masihtumbuh setelah menopause. Kira-kira 60% asimtomatik dan hampir 50% ditemukan secara kebetulan pada pemeriksaan ginekologik.TujuanPenelitian: Untuk mengetahui prevalensi mioma uteri berdasarkan umur dibandingkan dengan tumor ginekologi lainnya di RSUP Prof. Dr. R. D. Kandou Manado.Metode Penelitian:Desain deskriptif retrospektif menggunakan catatan rekam medik. Sampel pada penelitian ini adalah 401 kasus tumor ginekologi, 127 di antaranya kasus mioma uteri periode 1 Juli 2013-1 Juli 2014.Analisis data yang digunakanadalahanalisisunivariat.Hasil dan Kesimpulan:Darihasil catatan rekam medik pada periode 1 Juli 2013–1 Juli 2014, mioma uteri merupakan tumor ginekologi kedua terbanyak (31,7%). Dari 127 kasus yang paling banyak menderita mioma uteri adalah kelompok umur 41-50 tahun (56,7%). Prevalensi mioma uteri tertinggi pada kelompok umur 41-50 tahun (48,9%).Kata kunci:Tumor ginekologi, mioma uteri, prevalensi, umur